Keharmonisan Sosial dalam Fenomenologi Kehidupan sebagai Bentuk Perlawanan terhadap Individualisme: Social Harmony in the Phenomenology of Life as a Form of Resistance to Individualism - Pitang, Simon Pedro; Gobang, Paulus Whilfridus; Leu, Adrianus (Jurnal Filsafat Indonesia, 2025)
The research focuses on exploring the meaning of social harmony in human daily life in the midst of individualistic life. This exploration is based on the phenomenology of life according to Michel Henry through critical-philosophical reflection, as well as a little theological. For Henry, human consciousness always begins and is directed to the inner life; he feels himself and makes himself feel, this is called auto-affection. Inner experience becomes an important point for the phenomenology of life, but at the same time opens up opportunities for humans to realize the life that exists in others. Therefore, exploring the meaning of social harmony in this phenomenology will have an impact on the daily lives of humans who are bound by individualism. The method used in the research is a leatherative method through literature study. This research found that the phenomenology of life will produce intersubjectivity that encourages humans to pay attention to each other, as well as will have an impact on social ethics. The contribution of this research is to generate an attitude of care and love for others who are unique, valuable, and worthy, and create social harmony in everyday life.